Tracking a large‐scale and highly toxic Arctic algal bloom: Rapid detection and risk communication - Evangeline Fachon; Robert S. Pickart; Gay Sheffield; Emma Pate; Mrunmayee Pathare; Michael L. Brosnahan; Eric Muhlbach; Kali Horn; Nathaniel N. Spada; Anushka Rajagopalan; Peigen Lin; Leah T. McRaven; et al. (Limnology and Oceanography Letters)
Abstract In recent years, blooms of the neurotoxic dinoflagellate Alexandrium catenella have been documented in Pacific Arctic waters, and the paralytic shellfish toxins (PSTs) that this species produces have been detected throughout the food web. These observations have raised significant concerns about the role that harmful algal blooms (HABs) will play in a rapidly changing Arctic. During a research cruise in summer 2022, a massive bloom of A. catenella was detected in real time as it was advected through the Bering Strait region. The bloom was exceptional in both spatial scale and density, extending > 600 km latitudinally, reaching concentrations > 174,000 cells L−1, and producing high‐potency PST congeners. Throughout the event, coastal stakeholders in the region were engaged and a multi‐faceted community response was mobilized. This unprecedented bloom highlighted the urgent need for response capabilities to ensure safe utilization of critical marine resources in a region that has little experience with HABs.